The Earnings Effects of Multilateral Trade Liberalization : Implications for Poverty - Hertel, Thomas W.; Ivanic, Maros; Preckel, Paul V.; Cranfield, John A.L. (Washington, DC: World Bank, 2014)
Most researchers examining poverty and multilateral trade liberalization have had to examine average, or per capita effects, suggesting that if per capita real income rises, poverty will fall. This inference can be misleading. Combining results from a new international cross-section consumption analysis with earnings data from household surveys, this article analyzes the implications of multilateral trade liberalization for poverty in Indonesia. It finds that the aggregate reduction in Indonesia's national poverty headcount following global trade liberalization masks a more complex set of impacts across groups. In the short run the poverty headcount rises slightly for self-employed agricultural households, as agricultural profits fail to keep up with increases in consumer prices. In the long run the poverty headcount falls for all earnings strata, as increased demand for unskilled workers lifts incomes for the formerly self-employed, some of whom move into the wage labor market. A decomposition of the poverty changes in Indonesia associated with different countries' trade policies finds that reform in other countries leads to a reduction in poverty in Indonesia but that liberalization of Indonesia's trade policies leads to an increase. The method used here can be readily extended to any of the other 13 countries in the sample.